Protein structure, dynamics, and function—a 20th IUPAB Congress symposium - Garratt, Richard C. (Biophysical reviews, 2021)
A wide range of topics was raised by the four invited speakers who took part in the session on protein structure, dynamics, and function during the 20th IUPAB Congress. Most of the emphasis was placed on understanding the underlying biological phenomena of interest although applications in drug development were also mentioned. For both these purposes, it was clear that a complete description of the dynamics of the system was as important as the structures themselves. The subjects covered included antibiotic peptides, sodium channels, the synthesis of the bacterial cell wall, and protein dynamics using X-FELs.